2023
DOI: 10.1111/myc.13564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of candidemia in children at a university hospital: A retrospective cohort

Abstract: Despite improvements in diagnosis and treatment, candidemia remains a major cause of mortality and morbidity in hospitalised paediatric patients. 1,2 Candidemia causes a global public health concern due to prolonged hospital stays, high mortality rates, and increased costs, resulting in additional economic burden. 3,4 Over the years, Candida albicans (CA) has been the most common species, but there has been an increase in the prevalence of non-albicans Candida (NAC) spp. in recent years, including C. parapsilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The prevalence of invasive CPC candidiasis varies according to region, and nationwide multicentric data may not be available for many countries. A recent study conducted with retrospective data of candidemia over 14 years in Turkey revealed C. parapsilosis sensu lato as the most commonly isolated species, with a total of 148 isolates [ 46 ]. Liu et al [ 47 ] described 12 cases of CPC candidemia over a period of 11 years in a Canadian tertiary care pediatric hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of invasive CPC candidiasis varies according to region, and nationwide multicentric data may not be available for many countries. A recent study conducted with retrospective data of candidemia over 14 years in Turkey revealed C. parapsilosis sensu lato as the most commonly isolated species, with a total of 148 isolates [ 46 ]. Liu et al [ 47 ] described 12 cases of CPC candidemia over a period of 11 years in a Canadian tertiary care pediatric hospital.…”
Section: Discussionmentioning
confidence: 99%
“…However, corroboration of this effect was inconclusive in a subsequent independent cohort study conducted in France, which compared echinocandins and azoles as first-line antifungal therapy without reaching significance in multivariate analyses (Bienvenu et al, 2020). Aside from Candida auris, antifungal resistance is systematically led by non-albicans species in China (Zhang et al, 2020;Liu et al, 2021), South Korea (Kwon et al, 2021), Turkey (Guner Ozenen et al, 2023), Italy (Mazzanti et al, 2021), Thailand (Ngamchokwathana et al, 2021, and Saudi Arabia (Al-Dorzi et al, 2018), out of which, C. tropicalis represents the major contributor. Data on resistance/ susceptibility would appear to draw a trend of inverse sensitivity between compounds of the echinocandin group and fluconazole, with C. albicans displaying higher figures of resistance to echinocandin compounds than non-albicans species and lower figures of resistance to azole compounds than non-albicans species (Al-Dorzi et al, 2018;Jung et al, 2020;Guner Ozenen et al, 2023).…”
Section: Treatmentmentioning
confidence: 99%
“…Aside from Candida auris, antifungal resistance is systematically led by non-albicans species in China (Zhang et al, 2020;Liu et al, 2021), South Korea (Kwon et al, 2021), Turkey (Guner Ozenen et al, 2023), Italy (Mazzanti et al, 2021), Thailand (Ngamchokwathana et al, 2021, and Saudi Arabia (Al-Dorzi et al, 2018), out of which, C. tropicalis represents the major contributor. Data on resistance/ susceptibility would appear to draw a trend of inverse sensitivity between compounds of the echinocandin group and fluconazole, with C. albicans displaying higher figures of resistance to echinocandin compounds than non-albicans species and lower figures of resistance to azole compounds than non-albicans species (Al-Dorzi et al, 2018;Jung et al, 2020;Guner Ozenen et al, 2023). Nevertheless, it has been reported that empirical administration of high-dose liposomal amphotericin B (L-AmB) is associated with better management of fungal invasiveness, less ICU-acquired candidemia, less need for an antifungal agent additional to L-AmB, and ultimately a reduction in ICU mortality, emphasizing the feasibility and relative safety of a preemptive antifungal therapy strategy to combat bloodstream Candida colonization (Azoulay et al, 2017).…”
Section: Treatmentmentioning
confidence: 99%